2010
DOI: 10.1111/j.1600-0765.2010.01284.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic separation and characterization of keratinocyte stem cells from human gingiva

Abstract: The human gingival CD71(neg) cell fraction, separated by a magnetic system, demonstrated several characteristics of gingival keratinocyte stem cells. It is also suggested that a magnetic system may be an important tool in acquiring oral keratinocyte stem cells for research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 33 publications
2
31
0
1
Order By: Relevance
“…Basal keratinocytes expressing high levels of a 6 integrin or CD49f have been shown to display keratinocyte stem cell attributes, while low expressing a 6 cells are post-mitotic differentiating keratinocytes [26,27,47]. Subsequently, oral keratinocyte stem cells have been isolated from oral mucosa using this marker [48] and also according to their relative cells size [49]. The present study has demonstrated that the enrichment of clonogenic ERM cells can be successfully achieved on the basis of integrin a 6 expression, which was less expressed or lacking on clonogenic periodontal ligament stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Basal keratinocytes expressing high levels of a 6 integrin or CD49f have been shown to display keratinocyte stem cell attributes, while low expressing a 6 cells are post-mitotic differentiating keratinocytes [26,27,47]. Subsequently, oral keratinocyte stem cells have been isolated from oral mucosa using this marker [48] and also according to their relative cells size [49]. The present study has demonstrated that the enrichment of clonogenic ERM cells can be successfully achieved on the basis of integrin a 6 expression, which was less expressed or lacking on clonogenic periodontal ligament stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies in the oral mucosa used morphological and clonogenic characteristics to assert that cells isolated using putative stem cell markers were indeed stem cells. 30,31,32,33 …”
Section: Methods Used To Identify and Characterize Stem Cellsmentioning
confidence: 99%
“…In recent years, dramatic improvement in magnetic cell separation techniques has made it more popular for isolating target cells compared with the use of a flow cytometer. Magnetic separation might not affect the integrity and scrupulousness of DNA in nuclei because fluorescent dye is not used (9,10). This is a huge advantage to use magnetic separation for future regenerative medicine.…”
mentioning
confidence: 99%